Дизайн упаковки продуктів: від концепції до реалізації в Adobe Illustrator - Махортов, Д. Р. (ХНУРЕ, 2025)
This work is dedicated to evaluating the effectiveness of consumer goods packaging design, specifically focusing on identifying key criteria that influence attractiveness and convenience. It examines major market trends, increasing competition, and consumer requirements for modern packaging. The importance of utilizing innovative solutions and tools, such as Adobe Illustrator, for creating high-quality and functional packaging is discussed. The main stages of packag ing development are outlined, including concept creation, template design, print preparation, and design efficiency analysis. A comprehensive approach to pack aging development is proposed, which enhances product competitiveness in the market and contributes to increased sales.
Keywords: дизайн упаковки; упаковкаи продуктів